2022
DOI: 10.1038/s41556-021-00822-7
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine oxidation of copper transporter CTR1 drives VEGFR2 signalling and angiogenesis

Abstract: VEGFR2 (KDR/Flk1) signaling in endothelial cells (ECs) is essential for developmental and reparative angiogenesis. Reactive oxygen species (ROS) and copper (Cu) are also involved.in these processes. However, their inter-relationship is poorly understood. The role of endothelial Cu importer CTR1 in VEGFR2 signaling and angiogenesis in vivo is hitherto unknown. Here we show that CTR1 functions as a previously unrecognized redox sensor to promote angiogenesis in ECs. CTR1-depleted ECs showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 62 publications
1
74
0
Order By: Relevance
“…Similar to our finding, some studies have highlighted that SP1 and p53 often cooperate to regulate many tumor-related signaling pathways ( 41 ). In addition to transport copper and platinum, a recent study shows that CTR1 is rapidly sulfenylated at Cys189 at its cytosolic C terminus after stimulation with vascular endothelial growth factor (VEGF), which induces CTR1-vascular endothelial growth factor receptor type 2(VEGFR2) disulfide bond formation and their co-internalization to early endosomes, driving sustained VEGFR2 signaling to enhance angiogenesis ( 42 ). It is needed to explore further whether cytokines, like VEGF, have a possible function in the process of CTR1-mediated cisplatin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our finding, some studies have highlighted that SP1 and p53 often cooperate to regulate many tumor-related signaling pathways ( 41 ). In addition to transport copper and platinum, a recent study shows that CTR1 is rapidly sulfenylated at Cys189 at its cytosolic C terminus after stimulation with vascular endothelial growth factor (VEGF), which induces CTR1-vascular endothelial growth factor receptor type 2(VEGFR2) disulfide bond formation and their co-internalization to early endosomes, driving sustained VEGFR2 signaling to enhance angiogenesis ( 42 ). It is needed to explore further whether cytokines, like VEGF, have a possible function in the process of CTR1-mediated cisplatin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…ROS, especially H 2 O 2 , are transmitted by a redox sensor to facilitate the trafficking and signaling of VEGF receptor type 2, which is important for reparative angiogenesis. [ 28 ] In general, the formation and removal of cellular ROS are regulated by pro‐oxidant and antioxidant enzymes such as CAT, NADPH oxidases, SOD, etc, [ 28 ] contributing to maintain redox homeostasis and regulate normal cellular function. However, the role of oxidative stress in diabetic patients with critical limb ischemia is an imbalance between pro‐oxidative and antioxidant effects, leading to tissue and cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…The former is responsible for protein coding in humans (29). A recent study revealed that CTR1 could function as a redox sensor to drive neovascularization (30). A strong correlation between CTR1 and Programmed death-ligand 1 (PD-L1) paved the way for clinical trials to evaluate Cu chelators as immune checkpoint inhibitors (31).…”
Section: Discussionmentioning
confidence: 99%